Leucocytoclastic Vasculitis: A Rare Cause of Palpable Purpura - Das, Aparna; Hoque, AKM Aminul; Gupta, Ratan Das; Banik, Gobinda; Hossain, Md Yeanur; Islam, Moinul (Journal of Medicine, 2012)
Leucocytoclastic vasculitis (LCV) is an isolated condition without systemic vasculitis or glomerulonephritis. The skin is the most commonly involved organ in LCV, predominantly in the lower extremities. The most common skin manifestation is palpable purpura. Some patients may have arthralgias or arthritis as the presenting symptom, usually oligoarthritis of the knees or ankles. The inflammation of small blood vessels, most commonly postcapillary venules, is the cardinal histologic feature of LCV. A16-year-old male admitted into our medicine unit with palpable purpura. He was diagnosed as leukocytoclastic vasculitisof unidentified etiology on the basis of clinical conditions, laboratory tests, and histopathological analysis. Most important cause of LCV is drugs. So, we report this case to increase the awareness of indiscriminate use of medicine which can case this problems. DOI: http://dx.doi.org/10.3329/jom.v13i2.12770 J Medicine 2012; 13 : 240-242